Dividend Policy: Examining The Effect of Probability, Leverage, Firm Size, and Growth & Investment Opportunity - Evans Salim; Sawidji Widoatmojo (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of profitability, leverage, company size, and growth & investment opportunities on dividend policies from all non-financial companies listed on Indonesian Stock Exchange for the 2018-2020 period. This study generated 288 data from the 96 companies observed which met the purposive sampling criteria. Panel data regression, processed by EViews 10 is used as an analytical method for testing the hypotheses. To determine the best data estimation model, we utilized Chow Test and Hausman Test, which results pointed out that Fixed Effect Model is the most suitable for this study. Correlations and Glejser Test are also conducted beforehand, to ensure that both Multicollinearity and Heteroscedasticity are not present in this model. Research results found that profitability has a positive significant effect on dividend policy, leverage has a positive but insignificant effect on dividend policy, company size has a positive but insignificant effect on dividend policy, and lastly growth & investment opportunities has a negative but insignificant effect on dividend policy.